Hinduism and its sense of history - Sharma, Arvind (Oxford University Press, 2003)
It has been long taken for granted in the study of Hinduism over the past two centuries that the Hindus lacked a sense of history. This book marshalls evidence to render this assumption, which has had far-reaching consequences, implausible.